Irrigation drip and phosphorus managements in the rust coffee progress - Barbosa Junior, Mauro Peraro; Pozza, Edson Ampélio; Souza, Paulo Estevão de; Silva, Mirian de Lourdes Oliveira e; Pozza, Adélia Aziz Alexandre; Guimarães, Rubens José (Coffee Science - ISSN 1984-3909, 2017)
Rust is the most devastating disease of coffee. The rust intensity is affected by water supply and nutritional balance of plants. Thus the aim of this study was to evaluate the incidence of rust in coffee plantations with different management of irrigation and phosphorus fertilization. The study was carried out in Lavras-MG, with coffee cultivar MGS Crossing. Evaluations of the disease were carried out from March 2012 to November 2014. The experimental design was a randomized complete block design with twelve treatments, 3 fertilization managements with 4 drip irrigation management, in a fatorial scheme of variance analysis, with three replicates, totaling 36 plots. The results for the average of disease incidence during the evaluation period was plotted. The data were integrated into area under incidence progress curve (AUIPC). It was observed higher AUIPC (P <0.05) in the treatment without irrigation in 2013. The rust incidence progress was higher when phosphorus fertilization was not provided.